Development of Super Priority Tourism Destinations in Indonesia Through Human Resource Planning - Sekarani, Shalsyadila Safira; Gibran, Hafiizh Muhammad; Lestari, Silvy Dwi; Lestari, Rahayu; Hardini, Resti; Digdowiseiso , Kumba (CV ODIS, 2023)
This article discusses the importance of developing super-priority tourism destinations in Indonesia through human resource planning (HR). In Indonesia, there is still great potential for natural resources, culture, culinary and natural beauty that is not managed properly, and government initiatives supported by local communities can play an important role in developing this potential. Tourism in Indonesia is considered a strategic economic sector that can contribute significantly to economic growth, regional development, and improving community welfare. This article discusses the importance of the role of five types of tourism as a source of foreign exchange for the country, namely cultural, historical, natural, shopping, and religious tourism. Developing human resources in the tourism industry is essential to achieve sustainable tourism development goals and make a positive contribution to the local economy and society. Furthermore, this article highlights some of the leading destinations in Indonesia such as Lake Toba, Borobudur, Mandalika, Labuan Bajo, and Likupang, showing the importance of the role of quality human resource management in increasing the competitiveness of the tourism industry. Human resource management at the national and local levels, as well as the government's role in policy and strategic planning, are highlighted as key factors in maximizing Indonesia's tourism potential. This article contributes to a better understanding of how good human resource management can support the sustainable growth of the tourism industry and provide significant economic benefits to local communities in various tourist destinations in Indonesia.